2004
DOI: 10.1161/01.cir.0000124726.72615.60
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Mental Stress and Exercise on T-Wave Alternans in Patients With Implantable Cardioverter Defibrillators and Controls

Abstract: Background-Malignant cardiac arrhythmias can be triggered by exercise and by mental stress in vulnerable patients.Exercise-induced T-wave alternans (TWA) is an established marker of cardiac electrical instability. However, the effects of acute mental stress on TWA have not been investigated as a vulnerability marker in humans. Methods and Results-TWA responses to mental stress (anger recall and mental arithmetic) and bicycle ergometry were evaluated in patients with implantable cardioverter defibrillators (ICD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
3
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 37 publications
3
87
3
1
Order By: Relevance
“…This is not in disagreement with previous investigations, which also found that dynamics of TWA cannot be completely explained by changes in heart rate in patients with coronary artery disease. 32,33 Consistent with the relatively small changes in heart rate, there was also a small shortening of QT intervals before the onset of VTA (2.5%). Although correction of QT intervals with the use of Bazett's formula resulted in prolongation of QTc-B before the onset, this effect could be due to overestimation of QT intervals at faster heart rates.…”
Section: Changes In Cardiac Rhythm and Repolarization Instabilities Bmentioning
confidence: 63%
“…This is not in disagreement with previous investigations, which also found that dynamics of TWA cannot be completely explained by changes in heart rate in patients with coronary artery disease. 32,33 Consistent with the relatively small changes in heart rate, there was also a small shortening of QT intervals before the onset of VTA (2.5%). Although correction of QT intervals with the use of Bazett's formula resulted in prolongation of QTc-B before the onset, this effect could be due to overestimation of QT intervals at faster heart rates.…”
Section: Changes In Cardiac Rhythm and Repolarization Instabilities Bmentioning
confidence: 63%
“…20 Potential mechanisms include increases in sympathetic nervous system activity, leading to cardiac instability 21 and an acute increase in susceptibility to ventricular fibrillation and SCD. When we examined the associations between phobic anxiety and risk of CHD over time, only the association with SCD risk appeared to vary by time.…”
Section: Albert Et Al Phobic Anxiety and Risk Of Chd And Scd In Womenmentioning
confidence: 99%
“…Results revealed that SBP levels during metal task and SBP reactivity (increases) were highest for the severely ischemic group and lowest for controls (Krantz et al, 1991). Acute, laboratory-induced anger as part of a mental stress task has also been found to increase the risk of cardiac arrhythmias associated with sudden cardiac death in CAD patients with implantable cardioverter-defibrilators (Kop et al, 2004;Lampert, Jain, Burg, Batsford, & McPherson, 2000).…”
Section: Stress Reactivity In Chd Patientsmentioning
confidence: 98%